1995
DOI: 10.2307/2986196
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference for Masked System Lifetime Data

Abstract: Estimating component and system reliabilities frequently requires using data from the system level. Because of cost and time constraints, however, the exact cause of system failure may be unknown. Instead, it may only be ascertained that the cause of system failure is due to a component in a subset of components. This paper develops methods for analysing such masked data from a Bayesian perspective. This work was motivated by a data set on a system unit of a particular type of IBM PS/2 computer. This data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Goetghebeur and Ryan [17] addressed the problem of assessing covariate effects based on a semi-parametric proportional hazards structure for each failure type when the failure type is unknown for some individuals. Reiser et al [18] considered statistical procedures for analysing masked data, but their procedure Downloaded by [University of Colorado -Health Science Library] at 14:02 30 September 2014 could not be applied when all observations have an unknown cause of failure. Our model can be derived as follows.…”
Section: The Cwg Distributionmentioning
confidence: 99%
“…Goetghebeur and Ryan [17] addressed the problem of assessing covariate effects based on a semi-parametric proportional hazards structure for each failure type when the failure type is unknown for some individuals. Reiser et al [18] considered statistical procedures for analysing masked data, but their procedure Downloaded by [University of Colorado -Health Science Library] at 14:02 30 September 2014 could not be applied when all observations have an unknown cause of failure. Our model can be derived as follows.…”
Section: The Cwg Distributionmentioning
confidence: 99%
“…Real examples of RMCR data in the reliability context and medical research can be found in Dinse (1982), Reiser et al (1995), and Flehinger et al (2001). Sen et al (2001) and Flehinger et al (2001).…”
Section: Background On Rmcr Datamentioning
confidence: 99%
“…In engineering applications, one frequently encounters data where the cause of failure is not completely known (see Reiser et al 1995;Reiser, Flehinger, and Conn 1996). In reliability literature, such data are termed as masked failure data.…”
Section: Inference From Data With Missing Cause Of Failurementioning
confidence: 99%